Fauna and Distribution of Phytonematodes of Apple Orchards in the Northern Regions of the Surkhandarya Region of Uzbekistan - Sattorovich, Bekmurodov Abdujabbor; Isakjonovna, Abdujalilova Maftuna (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides data on the fauna and distribution of phytonematodes in the root soil and root system of apple plants in the northern regions of the Surkhandarya region of Uzbekistan. As a result of the research, 34 species of phytonematodes were identified, belonging to 21 genera, 13 families, 5 orders and 2 subclasses. Numerous species in the phytonematode fauna of apple plants were Cephalobuspersegnis, Chiloplacussclerovaginatus, Panagrolaimusrigidus, Aphelenchusavenae, Aphelenchoidesparietinus, A.composticola, A.limberi, andA.blasthophthorus.